Clinical characteristics and long-term outcomes in SLE–myositis overlap syndrome: a controlled retrospective cohort study - Güllü Sandal Uzun; David Isenberg (Rheumatology, 2026)
Abstract Objectives Systemic lupus erythematosus (SLE) with concurrent inflammatory myositis (IIM) has a distinct clinical phenotype, yet its impact on long-term outcomes has been poorly defined. We aimed to determine the risk of mortality, malignancy, and severe renal disease in a large SLE cohort stratified by the presence of myositis. Methods We conducted a retrospective analysis of prospectively maintained, single-center cohort of 855 SLE patients followed between 1978 and 2024. Patients were stratified into two groups: SLE without myositis (n = 819) and SLE-myositis overlap (n = 36). Demographic, clinical, serological, and long-term outcome data were compared. Survival was analyzed using the Kaplan–Meier method and multivariable using cox proportional hazards regression. The study was an audit, not requiring formal hospital ethics approval or individual consent, due to the observational retrospective nature of the study using de-identified data—no individualized or identifiable data are presented in this study. Results Myositis was identified in 4.2% (36/855) of the SLE cohort. The SLE-myositis overlap group was characterized by a higher proportion of patients of Afro-Caribbean ethnicity (38.9% vs. 16.8%; p < 0.001) a greater frequency of interstitial lung disease (ILD) (13.8% vs. 1.2%; p < 0.001) and higher rates of anti-RNP positivity (61.1% vs. 20.1%; p < 0.001). All-cause mortality over a median follow-up of 22.4 years was over two-fold higher in the SLE-myositis group (30.5% vs. 14%; log-rank p < 0.001). Multivariable Cox regression confirmed that the presence of myositis was an independent predictor of mortality. ILD (HR 5.5, 95% CI 3.61–9.6; p = 0.004) and malignancy (HR 3.1, 95% CI 2.9–11.6; p < 0.001) were also independently associated with increased mortality. Conclusion SLE–myositis overlap syndrome represents a clinically important subgroup characterized by a predominance of non-Caucasian patients and a higher burden of extra-renal disease.The presence of myositis is an important prognostic marker associated with increased long-term mortality in patients with SLE.